IMMUNOHISTOCHEMICAL EXPRESSION OF P16 IN LOW GRADE UROTHELIAL CARCINOMA - Chaudry, Muhammad Umer; Akhtar, Farhan; Jamal, Nighat; Mansur, Hamza; Sarwar, Nozaif; Saleem, Yusra (Pakistan Armed Forces Medical Journal, 2021)
Objective: To determine the frequency of Immunohistochemical expression of P16 in low grade urothelial carcinoma patients.Study Design: Cross sectional study.Place and Duration of Study: Department of Histopathology, Armed Forces Institute of Pathology, Rawalpindi, from May 2018 to Jul 2019.Methodology: A total of 120 formalin-fixed and paraffin embedded blocks from patients having low grade urothelial carcinomawere included in the study and were stainedimmunohistochemically with P16 antibody. Expression of P16 was noted by two independent pathologists and nuclear stain of strong intensity was taken as positive.Results: There were 91 (76%) males and 29 (24%) females with age range from 18-85 years (mean 67.19 ± 11.5 years) female to male ratio was 1:3. P16 stain was positive in (70.8%) and negative in 37 (31%) of low gradeurothelial carcinoma cases.Conclusion: The p-16 is expressed in a significant number of urothelial carcinomas (low grade) and this marker could be used in routine practice for early identification of patients at high risk of progression to advanced stage.